Desafios da formação continuada de professores para uso das TDIC na educação profissional e tecnológica - Miranda, Fernanda Machado de (2019)
The present work, developed under the Programa de Pós-graduação em Educação Profissional e Tecnológica (EPT) – research line: Teacher Training – aims to empower EPT high school teachers to develop the technological-pedagogical fluency and this way, acquire digital competences for the use of digital information and communication technologies as a pedagogical resource in the teaching and learning process. Grounded in Maguerez’s Arch problematization methodology, have structured actions for the planning, creation and implementation of a continuing training course in the semi-presential modality. In the beginning the work had as its target audience twenty-nine private institution teachers of the interior of Rio Grande do Sul, that teaches at occupational safety, aesthetics, nursing, radiology, administration and accounting technical courses and EJA. As data collection instruments, besides using the direct observation technique, two questionnaires were applied, one in the presential mode and the other ones like survey, self-applying, digitally available, with open questions. The result analysis was based on Bardin's content analysis theory, the data were categorized and compared with the relevant bibliographical references, promoting reflections on technological-pedagogical fluency and digital competences, along with the teaching knowledge of professionals in Vocational and Technological Education.